Lanna to Thai language translation (Thai) - Seresangtakul, Pusadee; Yaprom, Nikorn (Asia-Pacific Journal of Science and Technology, 2017)
The purpose of this research was to develop a Lanna to Thai language translation system. In order to develop the system, we created a Lanna to Thai dictionary. The dictionary comprises 7,497 Lanna words. The input of this system is a sequence of Lanna words, sentences and phrases. The input texts are segmented into sequences of Lanna words by using the longest matching algorithm. The Lanna sentences and phrases are analyzed and translated into the Thai language by using a hybrid of dictionary and Augmented Transition Networks (ATNs). We applied the Nondeterministic Finite Automata (NFA) to translate unknown words. In order to evaluate the efficiency of the system, 558 sentences of the Lanna Dharma script were input to test the system. The results of experiments showed that the correctness of the system is 83.69%.